The genetic footprint of the European Roma diaspora: evidence from the Balkans to the Iberian Peninsula - Ena, Giacomo Francesco; Giménez, Aaron; Carballo-Mesa, Annabel; Lišková, Petra; Araújo Castro E Silva, Marcos; Comas, David (Human genetics, 2025)
The Roma people have a complex demographic history shaped by their recent dispersal from a South Asian origin into Europe, accompanied by continuous population bottlenecks and gene flow. After settling in the Balkans around 1,000 years ago, the Roma gradually dispersed across Europe, and approximately 500 years ago, they established in the Iberian Peninsula what is now one of the largest Roma populations in Western Europe. Focusing specifically on the Iberian Roma, we conducted the most comprehensive genome-wide analysis of European Roma populations to date. Using allele frequency and haplotype-based methods, we analysed 181 individuals to investigate their genetic diversity, social dynamics, and migration histories at both continental and local scales. Our findings demonstrate significant gene flow from populations encountered during the Roma's dispersal and confirm their South Asian origins. We show that, between the 14th and 19th centuries, the Roma spread westward from the Balkans in various waves, with multiple admixture events. Furthermore, our findings refute previous hypotheses of a North African dispersal route into Iberia and genetic connections to Jewish populations. The Iberian Roma exhibit ten times greater genetic differentiation compared to non-Roma Iberians, indicating significant regional substructure. Additionally, we provide the first genetic evidence of assortative mating within Roma groups, highlighting distinct mating patterns and suggesting a gradual shift towards increased integration with non-Roma individuals. This study significantly enhances our understanding of how demographic history and complex genetic structure have shaped the genetic diversity of Roma populations, while also highlighting the influence of their evolving social dynamics.
Keywords: Romové; Haplotypes; tok genů; Španělsko; Humans; Genetic Variation; haplotypy; frekvence genu; Human Migration; genetická variace; Polymorphism, Single Nucleotide; jednonukleotidový polymorfismus; Spain; Gene Frequency; Gene Flow; Roma; lidé; populační genetika; migrace lidstva; Genetics, Population